Eastward enlargement of the European Union and the identity of Europe - Fuchs, Dieter; Klingemann, Hans-Dieter (2000)
Abstract: "The constitution of a European demos with a collective identity is one of the preconditions for adjusting the legitimacy problem of the European Union (EU). The analysis attempts to clarify empirically whether there is sufficient commonality regarding Europeans' political value orientations to substantiate a collective identity. Particularly in view of the European Union's eastward enlargement, the question arises whether widespread cultural heterogeneity in Europe allows the formation of a European demos at all. In Europe we can identify a West-East axis of political value orientations. Democratic attitudes decrease the further to the East while at the same time there is an increase in etatist orientations. Thresholds can be observed which distinguish western European countries on the one hand and central and eastern European countries on the other. Within the group of central and eastern Europe a further distinction can be made between the three Slavic republics of the former So